Multimodal pain stimulations in patients with grade B oesophagitis. Issue 7 (9th August 2005) - Drewes, A M; Reddy, H; Pedersen, J; Funch-Jensen, P; Gregersen, H; Arendt-Nielsen, L
Abstract : Aim: To obtain a better understanding of nociceptive processing in patients with oesophagitis. Patients and methods: Eleven patients with grade B oesophagitis were compared with an age and sex matched group of 16 healthy subjects. A probe was positioned in the lower part of the oesophagus. After preconditioning of the tissue, painful mechanical stimuli were applied as distensions with a bag using an impedance planimetric method. Distensions were done before and after pharmacological impairment of distension induced smooth muscle contractions. Thermal stimulation was performed by recirculating water at 1 and 60°C in the bag. The area under the temperature curve (AUC) represented caloric load. The referred pain area (being a proxy for the central pain mechanisms) to the mechanical stimuli was drawn at maximum pain intensities. Results: Patients were hyposensitive to mechanical stimuli, as assessed by the distending volume (F = 8.1, p = 0.005). After relaxation of smooth muscle with butylscopolamine, the difference between the two groups was more evident (F = 27.4, p<0.001). AUC for cold stimulation was 1048.6 (242.7) °C×s in controls and 889.8 (202.6) °C×s in patients (p = 0.5). For heat stimuli, AUC values were 323.3 (104.1) and 81.3 (32.3) °C×s in controls and patients, respectively (p = 0.04). The referred pain area to the mechanical stimulations was larger and more widespread in patients (49.3 (6.2) cm 2 compared with controls 23.9 (7) cm 2 ; p = 0.02). Conclusions: The data indicate that peripheral sensitisation of heat sensitive receptors and pathways combined with facilitation of central pain mechanisms may explain the symptoms in patients with oesophagitis.